The use of ecological and geographical analysis to create a predictive model of spread of quarantine adventives phytophages in Ukraine - Klechkovsky, Yu.; Titova, L.; Palagina, O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2018)
The methodology of ecological-geographical analysis of the distribution of quarantine adventitious phytophages and the construction of a prognostic model of their distribution in Ukraine is presented.